Effect of Business Location, Pricing Strategies, and Social Media Utilization on Income of Micro and Small Culinary Enterprises in Denpasar - I Putu Adi Pariartha; Surya Dewi Rustariyuni (Digital Innovation : International Journal of Management, 2025)
The rapid growth of Micro and Small Enterprises (MSEs) in the culinary sector in Denpasar City has made a significant contribution to the regional economy and job creation. This sector has become one of the key drivers of local economic activity, attracting both residents and tourists. However, despite its potential, challenges persist. Fluctuations in the number of MSE actors and the suboptimal use of social media for marketing hinder sustainable income growth. Moreover, poor decisions regarding business location and inappropriate pricing strategies often become barriers to achieving business success. This study aims to analyze the simultaneous effects of business location, pricing, and social media usage on the income of culinary MSEs in Denpasar City. A quantitative approach was employed using a survey method, in which questionnaires were distributed to 99 culinary MSE actors. The collected data were analyzed using multiple linear regression to evaluate the influence of each variable both simultaneously and partially. The results reveal that business location, pricing, and social media usage together have a significant effect on MSE income. Partially, business location and pricing show a positive and significant influence, indicating that strategic location selection and competitive pricing play crucial roles in increasing income. In contrast, social media usage does not significantly affect income, suggesting that while digital platforms have potential as marketing tools, their benefits remain limited without effective content strategies and adequate digital literacy. These findings highlight the importance of strengthening fundamental business aspects, particularly location and pricing strategies, to improve MSE performance. Furthermore, policy support and targeted assistance programs focusing on enhancing digital literacy and managerial capacity among MSE actors are essential. By addressing these areas, the culinary sector in Denpasar City can achieve more sustainable growth and contribute even more effectively to the local economy.